Xeroderma pigmentosum: a case series with ocular involvement - Belgaumkar, Vasudha A.; Chavan, Ravindranath B.; Salunke, Aarti S.; Patil, Pallavi P. (International Journal of Research in Dermatology, 2017)
Xeroderma pigmentosum (XP) is a rare, autosomal recessive disease caused by a defect in DNA repair. Patients with xeroderma pigmentosum often have cutaneous and ocular photosensitivity, freckle-like skin pigmentation, multiple skin and eye cancers, and, in some patients, progressive neurodegeneration. Xeroderma pigmentosum predominantly affects the UV exposed ocular surface, resulting in eyelid atrophy and cancers, corneal dryness, exposure keratopathy, and conjunctival tumors. Hereby, we report four cases of XP with ocular pathology. First case had ectropion, corneal abrasion, keratomalacia, and necrotic ulcer in periorbital area and second case had corneal opacity, conjuctival erythema and photophobia. The other two cases were siblings of second patient who also had photophobia. These cases illustrate the role of DNA repair in protection of the eyes from UV damage.